Factors Influencing Health Career Choices During Clinicians’ First Three Years in Practice - Darlow, Ben; Brown, Melanie; McKinlay, Eileen; Gray, Lesley; Pullon, Sue (Journal of Research in Interprofessional Practice and Education, 2022)
Background: Health systems globally need more clinicians to work rurally and in community-based primary care. This study explores factors influencing health graduates’ choice of clinical setting and geographical location during early careers, across a range of disciplines that work together to support the health of people in community-based and rural locations.Methods: Students from eight disciplines (n = 611) were recruited prior to their final year of pre-registration training. Data were collected via three electronic surveys completed at the end of participants’ first, second, and third year of clinical practice. Data were managed and analyzed with Template Analysis.Findings: Similar factors influenced clinical setting and location choice but differed in relative importance for each. The nature of the job itself was the most important factor influencing clinical setting choices. A broader range of influences were important to geographical location choices including personal reasons, the nature of the job, the nature of the location, and job availability and opportunities. Regulatory or training requirements limited choices available to some clinicians, particularly those from medicine.Conclusion: A range of complex and interacting factors influenced health graduates’ career choices. Findings indicate that a broad system-wide approach is needed to address community and rural health workforce needs.